Analisis Letak Sumber Air Rumah Tangga Di Wilayah Kerja Puskesmas Mijen, Semarang Terhadap Bakteri Escherichia Coli - Kanti Ratnaningrum; Merry Tiyas Anggraini; Pujangga P.Y. Dahlan (MAGNA MEDIKA: Berkala Ilmiah Kedokteran dan Kesehatan, 2015)
Analysis of the Location of Household Water Sources in the Working Area of Mijen Health Center, Semarang Against Escherichia Coli Bacteria Background: Case detection rate of diarrhea in Puskesmas Mijen, Semarang is still relatively high. One cause of diarrhea disease is a condition of polluted water sources such fouling proximity of water sources with a septic tank. Escherichia coli is a bacteria that may be found in contaminated water sources fouling. Coverage field of environmental health in terms of supervision and control of water quality in Puskesmas Mijen is still far from the achievement of the target, based on these data it is necessary to do research to analysis within a septic tank with a household water source for the presence of the bacterium Escherichia coli. Methods: This study is a cross-sectional study conducted in Puskesmas Mijen. The study methods using systematic random sampling method in 10 villages and the sample number were included with proportion estimate formula. Laboratory tests Escherichia coli bacteria levels in the water conducted in the laboratories of the Faculty of Medicine, Universitas Muhammadiyah Semarang. Data were analyzed using chi square test. Result: From the 36 samples of water, we get the result there is no significant relationship between the distance of a septic tank with a household water source for the presence of the bacterium Escherichia coli (P-value = 0.2). Conclusion: There is no related between the distance of the septic tank with a household water source within the findings of Escherichia coli bacteria in the household water in Puskesmas Mijen.